Micellar nanotubes dispersed electrokinetic chromatography for the simultaneous determination of antibiotics in bovine milk - Springer, Valeria Haydee (2012)
A method to determine four antibiotics for veterinary use (ciprofloxacin, enrofloxacin, florfenicol, and chloramphenicol) of different families (fluoroquinolones and amphenicols) in bovine milk was developed. The determination of the analytes was carried out using micellar electrokinetic capillary chromatography (MEKC) with a common sodium borate-SDS buffer solution containing single-walled carbon nanotubes (SWCNTs). In this way, a great improvement in the electrophoretic resolution and the separation efficiency was achieved compared to MEKC. An online reverse electrode polarity-stacking mode (REPSM) was carried out to enhance sensitivity. This step was performed in only 2 min and it allowed a stacked percentage of 103. That means that all the amount of injected analytes is effectively stacked. When this stacking procedure was combined with an off-line preconcentration step, based on SPE, analytes could be detected in lower concentration than the established maximum residue limits (MRLs). The LODs for the four compounds were between 6.8 and 13.8 μg L -1 and the RSD values were between 1.1% and 6.6%. The whole method was applied to spiked real samples with acceptable precision and satisfactory recoveries. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.